Effects of Environmental Factors on Growth and Artemisinin Content of Artemisia annua L. - Bui Thi Tuong Thu; Tran Van Minh; Boey Peng Lim; Chan Lai Keng (Tropical Life Sciences Research, 2011)
Seeds of two selected clones of Artemisia annua L., TC1 and TC2, were germinated in a greenhouse. Four-week-old seedlings from both clones were grown in the Thù Ðúc province of Ho Chi Minh City on 2nd January 2009 and Ðà Lat on 20th January 2009. During this study period in Thù Ðúc province, which is situated 4–5 m above sea level, was experiencing a tropical, dry season with temperatures ranging from 26.2°C– 32.8°C. Ðà Lat, situated at 1500–2000 m above sea level, was having temperate, dry season with lower temperatures, ranging from 10.5°C–18.0°C. The high temperatures and low elevation in Thù Ðúc Province led to slow vegetative growth for all of the plants from the two different clones and the artemisinin contents were significantly reduced. The temperate environment of Ðà Lat supported robustly growing plants, with plant heights and branch lengths 4–5 times taller and longer that those planted at Thù Ðúc Province. The artemisinin contents of A. annua planted at Ðà Lat were 3–4 times greater than those cultivated at Thù Ðúc Province. Hence, this study indicated that the variations observed in plant growth and artemisinin contents were due to temperature effects because the two selected clones were genetically homogenous. The cold weather of Ðà Lat was suitable for planting of A. annua as opposed to the tropical weather of Thù Ðúc Province. Biji benih bagi dua klon Artemesia annua yang terpilih, TC1 dan TC2, dicambah dalam rumah hijau. Anak benih berumur empat minggu bagi kedua-dua klon ini ditanam di provinsi Thù Ðúc di bandar Ho Chi Minh, pada 2 Januari 2009 dan Ðà Lat pada 20 Januari 2009. Dalam jangka masa kajian di provinsi Thù Ðúc, yang terletak 4–5 m atas paras air laut, telah mengalami musim tropika yang kering dengan suhu 26.2°C–32.8°C. Manakala Ðà Lat yang terletak di 1500–2000 m atas paras air laut mempunyai musim temperat yang kering dengan suhu yang lebih rendah, iaitu 10.5°C–18.0°C. Suhu tinggi dan paras tanah yang rendah di provinsi Thù Ðúc telah mengakibatkan kekurangan pertumbuhan vegetatif kesemua tumbuhan kedua-dua klon dan kandungan artemisinin dikurangkan secara bererti. Cuaca persekitaran temperat di Ðà Lat menyokong pertumbuhan yang kuat dan sihat dengan ketinggian pokok dan panjang ranting yang 4–5 kali lebih tinggi dan panjang berbanding dengan pokok yang ditanam di provinsi Thù Ðúc. Kandungan artemisinin dalam A. annua yang ditanam di Ðà Lat adalah 3–4 kali lebih banyak daripada pokok yang ditanam di provinsi Thù Ðúc. Maka kajian ini telah menunjukkan bahawa kevarianan dalam pertumbuhan pokok dan kandungan artemisinin adalah disebabkan oleh kesan suhu kerana kedua-dua klon yang terpilih adalah homogenus dari segi genetik. Cuaca sejuk di Ðà Lat didapati sesuai untuk penanaman A. annua berbanding dengan cuaca tropika di provinsi Thù Ðúc.